Correlation analysis of lipid profile and risk of diabetic nephropathy in patients with type 2 diabetes mellitus - St. Rahma; Sri Andriani Ibrahim; Jesica Mulyadi (Media Penelitian dan Pengembangan Kesehatan, 2026)
Background: Diabetic nephropathy is one of the most common microvascular complications in patients with type 2 diabetes mellitus and is closely related to changes in lipid profile. Objective: This study aimed to assess whether a significant relationship exists between lipid profile parameters and diabetic nephropathy among patients diagnosed with type 2 diabetes mellitus. Methods: This study used an observational analytical design with a retrospective cross-sectional approach involving 136 patients undergoing treatment at North City Health Centre, Gorontalo City, from September to December 2024. Lipid profile and nephropathy status data were collected through medical records, while statistical analysis included Mann–Whitney, Chi–Square, and Spearman's correlation tests. Results: The results showed significant differences in total cholesterol, LDL, triglycerides, and the total cholesterol/HDL ratio between the groups with and without diabetic nephropathy (p< 0.05), whereas HDL did not differ significantly. Spearman's correlation test showed that total cholesterol (r= 0.399), LDL (r= 0.300), triglycerides (r= 0.291), and the total cholesterol/HDL ratio (r= 0.316) were positively associated with nephropathy level, whereas HDL showed a non-significant negative correlation. Conclusion: These findings confirm that dyslipidaemia plays an essential role in the development of diabetic nephropathy and can be used as a clinical indicator for early detection. Monitoring and controlling lipid profiles is expected to help slow the progression of kidney damage in patients with type 2 diabetes mellitus.